Six-Year Retrospective Analysis of Epidemiology, Risk Factors, and Antifungal Susceptibilities of Candidiasis from a Tertiary Care Hospital in South China - Hazrat Bilal; Dongxing Zhang; Muhammad Shafiq; Muhammad Nadeem Khan; Canhua chen; Sabir Khan; Qian Wang; Lin Cai; Rehmat Islam; Haibin Hu; Yuebin Zeng (Microbiology Spectrum, 2023)
ABSTRACT Candidiasis is a life-threatening disease that increases mortality in critically ill patients. However, such epidemiological data are still lacking in underdeveloped regions of China. A retrospective analysis (2016 to 2021) was conducted in Meizhou People’s Hospital, China to study the burden of candidiasis, particularly candidemia, and antifungal susceptibilities of the species among hospitalized patients. Of the 7,864 candidiasis cases, 461 (5.86%) were candidemia cases. Candida albicans (64.25%) was the most identified species, followed by C. tropicalis (12.61%), C. glabrata (10.79%), and C. parapsilosis (9.79%). In non-C. albicans (NCA) candidemia cases, the number of C. glabrata cases was higher (102/461, 22.37%) than C. tropicalis (64/461, 14.04%). Gastrointestinal pathology, respiratory dysfunctions, septic shock, and malignancies were common underlying comorbidities, respectively. A central venous catheter was an independent risk factor for both C. albicans and NCA candidemia. The mortality rate was not statistically significant for either C. albicans or NCA. Amphotericin B and 5-flucytosine were highly effective (98 to 100%), while azoles were least effective (67.74 to 95.66%). Candidemia cases caused by C. tropicalis and C. glabrata had significantly lower azole susceptibility than non-candidemia-causing isolates. This study provides valuable information for prescribers to choose the right empirical therapy, for researchers to explore different resistance mechanisms, and for health care managers to control candidiasis better. IMPORTANCE This study provides important information on the burden of candidiasis, particularly candidemia, and the antifungal susceptibility of Candida species among hospitalized patients in an underdeveloped region of China. First, the finding that azoles were least effective against Candida species causing candidemia is particularly noteworthy, as it suggests the possibility of resistance to this class of antifungal agents. This information can guide the choice of empirical therapy and help in the selection of appropriate antifungal agents for the treatment of candidemia, thereby reducing the risk of resistance development. Second, the study provides important information for researchers to explore different resistance mechanisms in Candida species. Finally, the study has important implications for health care managers in controlling the spread of candidiasis. The high prevalence of candidemia cases in the study highlights the need for appropriate infection control measures to prevent the spread of the disease.